The well-fit for the FET model: understanding training transfer factors in Spain - Quesada Pallarès, Carla (2022)
Learning transfer evaluation is a necessary process for practitioners to assess the effectiveness of training, and the outcomes of training produces in workers’ behaviors. In this paper, we explore an alternative way to evaluate transfer: through the study of transfer facilitators and barriers. Our aim is to validate the Factors to Evaluate Transfer (FET) model in a large sample of Spanish employees using confirmatory factor analysis. We applied the Spanish version of the FET scale to a sample of 2,745 Spanish workers of public service institutions and private companies. The results show a seven-factor model as the best choice according to the adjustment indices presented in the paper. We obtained a shorter version of the instrument, with adequate construct validity as well as good reliability and internal consistency. This model is a step forward in the measurement of indirect transfer and allows keeping working on the FET model to diagnosis transfer factors and increase the probabilities of higher learning transfer levels.